Morphological variability and genetic potential of henna (Lawsonia inermis) germplasms in semi-arid regions of Rajasthan - B, NOOR MOHAMED M; SHUKLA, A K; A, KEERTHIKA; GUPTA, DIPAK KUMAR; JANGID, B L; ROY, P K; MEHTA, R S; KHANDELWAL, VIKAS (The Indian Journal of Agricultural Sciences, 2023)
Henna (Lawsonia inermis L.) is a commercial and export-oriented important perennial shrub used in the ornamentation of palm, feet, dyeing of hair, etc. Developing high-yielding varieties and elite plant materials are the best method to increase the productivity and quality in henna. An experiment was conducted at research farm of ICAR-Central Arid Zone Research Institute, Regional Research Station, Pali-Marwar, Rajasthan during 2018–22 in Randomized block design to assess variability among morphometric traits and genetic parameters for dry leaf yield and attributing characters in Henna. The results indicated that among 19 germplasms maximum dry leaf yield and minimum number of inflorescence was recorded in CZ-RSPH-8 followed by CZ-RSPH-15. The accession CZ-RSPH-9 (2.33%) exhibited the highest lawsone content (%) followed by CZ-RSPH-8 and CZ-RSPH-15. The estimates of phenotypic co-efficient variation (PCV) were higher than the respective genotypic co-efficient variation (GCV). The number of inflorescences registered high heritability with high genetic advance. Path analysis exhibited the direct effect of the number of inflorescence with dry leaf yield. Cluster analysis revealed two major clusters classified into 6 and 13 germplasm which depicts the diverse degree of relatedness among different accessions.